Gambaran Kesehatan Lingkungan dan Perilaku Hidup Bersih dan Sehat (PHBS) dalam Perbaikan Masalah Gizi Balita Stunting di Kecamatan Liang Anggang - Yudistira, Sigit; Pajrina, Nur; Khairunnisa, Khairunnisa; Salsabila, Adelia; Sa'adah, Nurlatifah; Arianti, Alda Rina; Wati, Ratna Dewi; Jidiwan, Jidiwan (Jurnal Kesehatan Indonesia, 2024)
Stunting is a disorder of growth and development of children due to chronic malnutrition and repeated infections, which is characterized by their length or height being below the established standard. Stunting is a problem because it is associated with an increased risk of illness and death, a higher risk of being susceptible to non-communicable diseases, suboptimal brain development so that motor development is delayed and mental growth is inhibited. Risk factors for stunting consist of 2 factors, namely direct factors such as food intake and infection, and indirect factors such as environmental health and clean and healthy living behavior (PHBS). This study aims to identify environmental health conditions and PHBS in stunted toddlers in overcoming the problem of stunted toddler nutrition. This type of research is qualitative which is analyzed descriptively and in-depth interviews and observations with research samples being mothers of stunted toddlers from Liang Anggang District (Landasan Ulin Barat, Selatan, Tengah, and Utara Villages). The sampling technique was carried out using the accidental sampling technique. This research was conducted in Liang Anggang District, Banjarbaru City. The results of the study showed that environmental health conditions in Liang Anggang District including water, sanitation, and hygiene wash factors were quite good. The condition of PHBS in households in Liang Anggang District is quite good. There needs to be awareness from the community where the task of forming this awareness is held by health workers who synergize with the community itself so that the community is more aware and pays attention to environmental health and PHBS to avoid stunting.